Manual of traumatic brain injury management - Zollman, Felise S. (Demos Medical Pub., 2011)
Pocket-sized and portable, the Manual of Traumatic Brain Injury Management provides relevant clinical information in a succinct, readily accessible format. Expert authors drawn from the fields of rehabilitation medicine, neurology, neurosurgery, neurophysiology, physical and occupational therapy, and related areas cover the range of TBI, from concussion to severe injury. Organized to be consistent with the way TBI is managed, the book is divided into six sections and flows from initial injury through community living post-TBI, allowing clinicians to key in on specific topics quickly. Manual of.